Takaful in Pakistan and Somalia: A Comparative Study of Regulatory Evolution and Market Development - Muhammad Akbar Khan; Abdirahman Said Ahmed (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
Islamic insurance (takaful) is practiced in both Somalia and Pakistan; however, the two countries differ markedly in their regulatory frameworks, operational models, and levels of market penetration, while also sharing certain structural similarities. This study undertakes a comparative legal and institutional analysis to examine these divergences and convergences and to identify opportunities for strengthening takaful development in both jurisdictions. As a Shariah-compliant alternative to conventional insurance, takaful is founded on principles of mutual risk sharing and collective responsibility. The analysis highlights distinct contextual challenges and prospects. In Somalia, the absence of conventional insurance creates both a necessity and an opportunity for takaful expansion, contingent upon improvements in political stability, economic conditions, and the gradual transition from traditional tribal risk-sharing mechanisms to formal insurance institutions. In contrast, Pakistan represents a more developed insurance environment, where takaful operates alongside conventional insurance under a relatively comprehensive regulatory framework. By comparing regulatory structures, market practices, and socio-economic conditions, this study demonstrates the potential economic and social contributions of takaful in both contexts. It concludes with policy-oriented recommendations aimed at enhancing regulatory effectiveness, market growth, and public awareness of takaful as a sustainable insurance alternative.